Integration Perceived Risk, Travel Constraints, and Social Influences in Theory of Planned Behavior - Komang Endrawan Sumadi Putra; Ni Nyoman Kerti Yasa; Tjokorda Gde Raka Sukawati; I Gst Ngurah Jaya Agung Widagda (International Journal of Social Science and Business, 2023)
One of the most intriguing research areas is consumer psychology and behavior, which has attracted increasing attention in recent years from marketing and tourism scholars as well as from experts in the sector and destination managers. This paper is a literature review of several articles regarding the application of perceived risk, constraints faced and social influences in the theory of planned behavior. The aim of this paper is to ensure that perceived risk, travel constraints and social influences can be integrated within the framework of the theory of planned behavior (TPB), as one of the most widely used socio-psychological models in the literature. Especially with regard to feasibility in the framework of tourism management. Based on a comprehensive TPB literature review using the systematic literature review method, the search yielded 65 articles from 23 indexed journal publications on Google Schoolar. The study results conclude that perceived risk, travel barriers, and social influence can be clearly applied within the theoretical framework of planned behavior (TPB). With the Covid 19 pandemic, it was found that more and more tourism articles applied the perceived risk variable and the constraints faced by tourists in their decision to visit a tourist spot.